Paracladopelma Harnisch from the Sino-Indian Region (Diptera: Chironomidae) - Yan, Chuncai; Jin, Zhaohui; Wang, Xinhua (Zootaxa, 2008)
The genus Paracladopelma Harnisch from the Sino-Indian region is reviewed. Five new species, P. binum, P. bui, P. cirratum, P. crenum, and P. digitum are described and illustrated as males. Five species, P. aratrum Chaudhuri et Chattopadhyay, P. furudoprimum Sasa et Arakawa, P. hibarasecundum Sasa, P. simantodeea Sasa, Suzuki et Sakai, and P. tamahikawai Sasa are reexamined. Parachironomus tamanipparai (Sasa) is again placed in Paracladopelma. P. tokaradiea Sasa et Suzuki is a new synonym of P. kuramaclarum Sasa. Five species, P. daitoijea Sasa et Suzuki, P. inaheia Sasa, Kitami et Suzuki, P. misumaiprima Sasa et Suzuki, P. tokaraefea Sasa et Suzuki, and P. tonewabea Sasa et Tanaka are placed in the genus Cryptochironomus as new combinations. P. laminatum (Kieffer) is recorded for the first time from China. A key to all known males of Paracladopelma is presented.